Wawasan Alquran tentang Ukhuwwah
Ukhuwwah in Islam has the aim of eliminating competition between individuals, tribes, excessive self-love, ego traits and animating the spirit of mutual help, working together and loving each other on the basis of love because of Allah Swt. and His Messenger. Besides that, ukhuwwah can also eliminate fanaticism (asabiyyah). In Islam, humans are considered special because of their devotion. The Prophet made ukhuwwah a strong bond, not just an expression. Actions that are tied to the relationship of blood and possessions and recognition will be created by mutual love, high sacrifice that is engraved on a good role model, namely Rasulullah Saw. Ukhuwwah dalam Islam memiliki tujuan yaitu menghilangkan persaingan antar individu, suku, cinta diri yang berlebihan, sifat ego dan menghidupkan spirit saling membantu, bekerja sama dan saling mencintai dengan dasar cinta karena Allah Swt dan Rasul-Nya. Selain itu ukhuwwah juga dapat menghilangkan fanatisme (as